S16 A Randomised Controlled Trial Of Atorvastatin As A Stable Treatment In Bronchiectasis. (10th November 2014) - Mandal, P; Chalmers, J; Sidhu, M; Davidson, D; Rossi, A; Hill, A
Abstract : Background: Bronchiectasis is characterised by chronic cough, sputum production, and recurrent chest infections. Pathogenesis is poorly understood, but excess neutrophilic airway inflammation is seen. Evidence suggests that statins have pleiotropic effects; therefore these drugs could be a potential anti-inflammatory treatment for patients with bronchiectasis. We did a proof-of-concept randomised controlled trial to establish if atorvastatin could reduce cough in patients with bronchiectasis. In addition, we wanted to establish the anti-inflammatory mechanisms of statins contributing to this. Methods: Patients aged 18–79 years were recruited from the Royal Infirmary of Edinburgh. Participants had clinically significant bronchiectasis confirmed by chest CT and two or more chest infections in the preceding year. Individuals were randomly allocated to receive either atorvastatin (80 mg) or a placebo, orally once a day for 6 months. Primary endpoint was reduction in cough from baseline to 6 months, measured by the Leicester Cough Questionnaire (LCQ) score (range 3–21; 3 severe cough; minimum clinically important difference, 1·3 units). Findings: (i) RCT 30 individuals were assigned atorvastatin and 30 were allocated placebo. There was evidence of a difference in baseline to 6-month change in LCQ between the treatment groups, with a significant improvement in the statin treated group, with a mean difference 2.2, 95% CI for difference (0.5, 3.9) p = 0.01. When analysed as proportion of improvement in LCQ, in the statin treated group 40% patients had a 1.3 Units or more improvement in the LCQ compared with 17% in the placebo group; difference in proportion 23% (95% CI for difference 1%, 45%), p = 0.04. There was significantly increased number of apoptotic airway neutrophils [mean difference of 8.9 (11.7); p = 0.04] with a trend towards a decreased total number of neutrophils in the sputum; p = 0.09; in statin treated group. (ii) In vitro studies Statins enhance apoptosis of neutrophils in vitro due to a reduction in stimuli induced increase in calcium flux. Interpretation: 6 months of atorvastatin improved cough on a quality-of-life scale in patients with bronchiectasis. Multicentre studies are now needed to assess whether long-term statin treatment can reduce exacerbations. Further studies are needed to establish if statins regulate Ca 2+ flux by altering the intracellular or extracellular pathways.